PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS IIA PADA MATERI SIMBOL DAN NILAI-NILAI SILA PANCASILA DI SD ISLAM MARYAM SURABAYA - Erwita Kristianingsih; Yuni Gayatri; Ni Luh Putu Sari Murthi (Universitas Muhammadiyah Surabaya, 2024)
This research aims to improve the learning outcomes of class IIA students at Maryam Islamic Elementary School through the application of the Problem Based Learning model on the Symbols and Values ​​of Pancasila Principles. The type of research used is quasi-experimental research. The research design is a post-test only control group design. The subjects of the research carried out were 28 class IIA students at Islam Maryam Elementary School, totaling 27 people for the 2023/2024 academic year. Data collection techniques are by means of observation and tests. The research instruments used learning implementation observation sheets, cognitive test sheets, and work result observation sheets. Data analysis was carried out using descriptive and qualitative statistics. The results of this research show that all stages of Problem Based Learning were carried out well, the results of observations of students' attitudes showed 100% fulfilled the KKTP, student learning results showed 92. 59% met the KKTP, the results of students' skills in 100% met the KKTP. The results of the reflection showed that all students felt happy and could understand the material being taught. The conclusion of this research is that the application of the Problem Based Learning model is effective in improving student learning outcomes.